Ultrasonically enhanced flux-less bonding with Zn-5Al alloy under ambient condition for high-temperature electronics interconnects. (January 2022) - Liu, Canyu; Liu, Allan; Su, Yutai; Chen, Yi; Zhou, Zhaoxia; Liu, Changqing
Abstract: Zn-5Al eutectic alloy is a promising Pb-free solder suitable for high-temperature electronics packaging. However, the soldering with Zn-5Al alloy is undermined by its poor oxidation resistance and wettability in ambient atmosphere, which also demands significant time to complete if transient liquid phase soldering (TLPS) is required. In this work, the TLPS assisted by ultrasonic vibration (USV) under ambient condition without flux has been performed to enhance and accelerate interfacial reactions between Zn-5Al and Cu or Ni substrate. It has been found that the resultant full intermetallic compounds (IMCs) joints with uniform microstructure can be formed within 1 min and 3 min on Cu and Ni substrate, respectively, without flux or protective inert gases. The IMCs resulted from the interfacial reactions have been identified after the completion of TLPS process. For the ultrasonic-assisted TLPS (U-TLPS) of Zn-5Al onto Cu substrate, the joints consist of three IMC layers, CuZn, Cu5 Zn8, and CuZn with the residual oxide fragments remained at the central line inside of IMC Cu5 Zn8, where Al is rich likely due to the segregation of element Al during the TLPS process. For the U-TLPS of Zn-5Al onto Ni substrate, three IMC layers, Ni5 Zn21, NiAl and Ni5 Zn21 IMC were also observed, with the porous Ni5 Zn21 IMC layers present in adjacent to the Ni substrate. Both residual oxide fragments in the Zn-5Al/Cu joints and porous Ni5 Zn21 IMC in the Zn-5Al/Ni joints could potentially deteriorate mechanical integrity of the joints, which is yet to be understood. Graphical abstract: Unlabelled Image Highlights: Zn-5Al was bonded onto Cu and Ni substrate without flux under ambient condition. Soldering time was significantly shortened by applying ultrasonic vibration. Formation and microstructure of IMCs at the interfaces are characterized. Mechanisms for ultrasonically assisted formation of Zn-5Al joints are proposed.